Is the European Union moving towards a strategic development of radio spectrum policy? A review of the Connected Continent legislative proposal - Maria Massaro; Erik Bohlin (International Telecommunications Society (ITS), 2014)
The new smartphone era is challenging the leading position the European Union (EU) has been occupying in the mobile economy, falling behind other economies such as the United States and some countries in the Asia-Pacific region. The EU acknowledges the fragmented structure of the electronic communications market as being one of the main obstacles to LTE deployment. The EC argues that a main source of fragmentation is lack of harmonised conditions governing the use of radio spectrum across the EU. The EU member states have developed different and sometimes conflicting radio spectrum management practices through time. A consequent drawback is the impossibility of providing wireless broadband dervices across national borders and of deploying the necessary wireless networks and radio equipment. In consequence, on 11 September 2013, the European Commission put forward a new legislative package for a 'Connected Continent: Building a Telecoms Single Market' which contains several reforms directed to create a single telecommunications market. Some of the proposed reforms would partly modify the existing regulatory system of the radio spectrum, introducing harmonised conditions governing national assignment procedures. Through a document analysis and selected experts interviews the paper attempts to assess whether the EU is moving towards a strategic development of radio spectrum policy by looking at the EU initiatives on radio spectrum since the beginning in 1987. Then the focus is narrowed down to the Connected Continent legislative proposal, to value its contribution to the harmonisation of national assignment procedures. The historical overview of the EU radio spectrum policy shows that the EU has gradually acknowledged the negative implications of national fragmented and inconsistent radio spectrum governing rules. The EU has become aware of the need for a long-term strategy for the planning of the use of radio spectrum for the creation and functioning of the EU internal market. However, the paper also claims that in the arduous process of harmonisation of radio spectrum use much has still to be accomplished. Furthermore the paper draws the conclusions that the radio spectrum reforms contained the Connected Continent legislative proposal are probably not the means by which the harmonisation of radio spectrum use for the completion of the internal market can be enhanced. The EU and the EU member states have remarkably diverging and conflicting views on the content of the EC proposed reforms. The EU member states are unwilling to give up on their prerogatives on the radio spectrum by accepting too intrusive harmonised measures.
Keywords: 330